Kredit Macet dan Debt Collector; Legalitas dan Dampaknya dalam Mengelola Risiko Kredit Macet Perbankan - Jakobus Anakletus Rahajaan; Sarifa Niapele (Journal of Business Application, 2024)
This research examines the normative legal validity of the debt collector profession through a normative legal approach using qualitative methods and analyzing primary, secondary, and tertiary legal materials. The study finds that non-performing loans (NPLs) pose a significant threat to banking stability, as increasing levels of bad debt can hinder banks' ability to achieve optimal profits. Banks often employ debt collectors to manage time and cost-effectively to address this. Debt collectors are legally recognized under Indonesian law, including the Civil Code, SEBI Number 14/17/DASP/2012, and the 2014 Bank Indonesia Regulation issued by OJK. Their role is supported by legal principles such as freedom of contract, consensualism, and pacta sunt servanda. Despite common misconceptions, debt collectors are legitimate professionals crucial for maintaining financial stability. Debtors should cooperate with debt collectors to resolve their debts rather than viewing them negatively.